THE ANALYSIS OF EXISTING CAR ENGINES FOR DETECTION THE MOST ECOLOGICAL - Ісьєміні, Ілля Ігорович; Баканов, Андрій Сергійович; Кірсенко, Сергій Анатолійович (Eastern-European Journal of Enterprise Technologies, 2012)
In the article the basic types of modern car engines are considered, their influence at the environment is examined and the most ecological of them are detected.